EFFECT OF SOWING TIME IN COTTON (GOSSYPIUM HIRSUTUM L.) ON BOLL DISTRIBUTION, CELLULOSE RATIO AND FIBER QUALITY - Vedat Beyyavas; Cevher Ilhan CEVHERI; Ahmet YILMAZ (Journal of Animal and Plant Sciences, 2024)
The growth, flowering, square and boll formation of cotton plant are significantly affected by sowing time and fruiting distributions. This study was carried out in order to determine the effect of sowing time and fruiting distribution on fiber yield and fiber quality in cotton under GAP region that semi arid ecolojical conditions of Türkiye at 2017 and 2018 cotton growing seasons. The Experiments were planned according to split plots experimental design with three replication in both years. At the study, Candia and Lima cotton varieties were used as plant material. Cotton seeds were sown on 5 May (normal sowing) and 10 June (late sowing) using a pneumatic seeder in both years. At the study, the number of bolls (per plant-1), yield per plant (g plant-1), boll weight (g), ginning outturn (%), holocellulose, cellulose, scan viscosity and polymerization degree were studied. According to the research; the number of bolls, boll weight and fiber yield were higher in normal planting than late planting. The low positional sympodial branch (1-5 fruit branches) boll position was better in the number of bolls and middle positional sympodial branch (6-10 fruit branches) was better in boll weight compared to other positions. The fiber yield obtained in low positional sympodial branch (1-5 fruit branches) and middle positional sympodial branch (6-10 fruit branches) positions was higher than the upper positional sympodial branch position (11 and higher fruit branches). The effects of sowing times and cultivars on cellulose and holocellulose rations were statistically insignificant. The cellulose ratio (94.40) obtained in the upper positional sympodial branch position (11 and higher fruit branches) in the first year was higher than the other sympodial positions, while the effect of boll position was statistically insignificant in the second year of the experiment.
Keywords: Cotton; sowing date; boll position; boll weight; fiber quality